2000
DOI: 10.1111/j.1528-1157.2000.tb00159.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial EEG Seizure‐Onset Patterns in Neocortical Epilepsy

Abstract: Summary: Purpose:We investigated neocortical seizureonset patterns recorded by intracranial EEG with regard to anatomic location, pathologic substrate, and prognostic >slue for surgical outcome.Methods: Seizure onset was analyzed in 53 neocortical resective epilepsy surgery patients. Anatomic location was divided into temporal and extratemporal. Pathologic substrate was classified as developmental, mature, and negative or nonspecific gliosis. Onset frequency was categorized by visual analysis into tradition EE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(185 citation statements)
references
References 19 publications
10
171
4
Order By: Relevance
“…Quantitative ictal subdural EEG analysis was performed, using spectral analysis similar to that in previous reports (Alarcon et al, 1995;Gotman et al, 1993Gotman et al, , 1995Wu and Gotman, 1998), based on the assumption that epileptic seizures are represented as sustained and synchronized rhythmic ictal discharges with certain frequencies on the EEG (Lee et al, 2000) and that the ictal discharges within the first epoch are stationary. In short, the ictal EEG magnitude within a preset frequency band (including the ictal discharge frequency at the first epoch) was the main parameter on ictal EEG analysis in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative ictal subdural EEG analysis was performed, using spectral analysis similar to that in previous reports (Alarcon et al, 1995;Gotman et al, 1993Gotman et al, , 1995Wu and Gotman, 1998), based on the assumption that epileptic seizures are represented as sustained and synchronized rhythmic ictal discharges with certain frequencies on the EEG (Lee et al, 2000) and that the ictal discharges within the first epoch are stationary. In short, the ictal EEG magnitude within a preset frequency band (including the ictal discharge frequency at the first epoch) was the main parameter on ictal EEG analysis in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Ictal EEG recordings were visually reviewed in the referential and bipolar montages by two electroencephalographers (EA and AS), who obtained a consensus for each electrode to determine whether it should be classified as being part of the seizure-onset zone. Seizure onset was defined as a sustained rhythmic change in the EEG accompanied by subsequent clinically typical seizure activity, not explained by level of arousal, and clearly distinguished from background EEG and interictal activity (Lee et al, 2000;Spencer et al, 1992). Some types of initial EEG changes before seizure onset including brief bursts of spikes and periodic spikes at a frequency of <2 Hz were not considered part of seizure onset for this analysis, according to the concept described by Lee et al (2000), who reported that brief bursts of spikes and slow periodic spikes are often seen interictally without clinical symptoms and do not necessarily indicate epileptic seizures.…”
Section: Visual Analysis Of Ictal Subdural Eeg Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The electrographic onset, defined as sustained rhythmic discharges which cannot be explained by physiological changes or state changes and which resulted in the habitual clinical seizures (Gotman et al, 1993), was derived from the clinical EEG report and evaluated by the authors (MZ, JJ, filter 0.3-70 Hz). When the rhythmic discharge was preceded by a change in spikes, as can be seen in mesiotemporal epilepsy, the onset rhythmic discharge was taken as the seizure onset (Lee et al, 2000). This moment was marked within the EEG, as well as 10 s before the first EEG change and 5 s after the first EEG change.…”
Section: Marking Hfos and Spikes During And Before Seizuresmentioning
confidence: 99%
“…But these features are commonly used to identify the seizure onset zone (SOZ), so long as the changes are relatively focal in one or a small number of electrodes and are recorded before the first clinical sign. Low-voltage fast activity [2][3][4][5] is the most commonly reported IOP in neocortical epilepsy, and low-frequency high-amplitude repetitive spiking is the most commonly reported IOP in mesial temporal lobe epilepsy (mTLE). Delta activity is usually held to be a spread pattern rather than a true IOP from the SOZ.…”
Section: Conventional Analysis Of Ieegmentioning
confidence: 99%